"Sometimes we can't fix things": a qualitative study of health care professionals' perceptions of end of life care for patients with heart failure. Issue 1 (December 2016) - Glogowska, Margaret; Simmonds, Rosemary; McLachlan, Sarah; Cramer, Helen; Sanders, Tom; Johnson, Rachel; Kadam, Umesh; Lasserson, Daniel; Purdy, Sarah
Abstract Background Although heart failure has a worse prognosis than some cancers, patients often have restricted access to well-developed end of life (EoL) models of care. Studies show that patients with advanced heart failure may have a poor understanding of their condition and its outcome and, therefore, miss opportunities to discuss their wishes for EoL care and preferred place of death. We aimed to explore the perceptions and experiences of health care professionals (HCPs) working with patients with heart failure around EoL care. Methods A qualitative in-depth interview study nested in a wider ethnographic study of unplanned admissions in patients with heart failure (HoldFAST). We interviewed 24 HCPs across primary, secondary and community care in three locations in England, UK – the Midlands, South Central and South West. Results The study revealed three issues impacting on EoL care for heart failure patients. Firstly, HCPs discussed approaches to communicating with patients about death and highlighted the challenges involved. HCPs would like to have conversations with patients and families about death and dying but are aware that patient preferences are not easy to predict. Secondly, professionals acknowledged difficulties recognising when patients have reached the end of their life. Lack of communication between patients and professionals can result in situations where inappropriate treatment takes place at the end of patients' lives. Thirdly, HCPs discussed the struggle to find alternatives to hospital admission for patients at the end of their life. Patients may be hospitalised because of a lack of planning which would enable them to die at home, if they so wished. Conclusions The HCPs regarded opportunities for patients with heart failure to have ongoing discussions about their EoL care with clinicians they know as essential. These key professionals can help co-ordinate care and support in the terminal phase of the condition. Links between heart failure teams and specialist palliative care services appear to benefit patients, and further sharing of expertise between teams is recommended. Further research is needed to develop prognostic models to indicate when a transition to palliation is required and to evaluate specialist palliative care services where heart failure patients are included.